Innovators in Digital News - Küng, L (I.B.Tauris, 2015)
News organisations are struggling with technology transitions and fearful for their future. Yet a cadre of these institutions – some new, some old – has emerged who are succeeding with digital news. Why are Vice and BuzzFeed investing in journalism and why are pedigree journalists joining them? Why are established news organisations letting experienced journalists go but recruiting technologists? This book looks at several key players in the digital news industry – including the Guardian, the New York Times, Quartz, BuzzFeed and Vice – and draws on extensive first-hand research inside the organisations. How do they operate? How do they innovate? This book identifies and discusses the common elements that underlie their success, and provides valuable pointers for how all players, legacy and clean sheet, can seize the growth potential that digital markets present.